The effect of mental imagery and physical exercise on static balance in subjects with multiple sclerosis - Mehrzad Kharestani; Ahmad Ghotbi Varzaneh; Mojtaba Esmaeeli Abdar (Vesnu Publications, 2015)
Introduction: Mental imagery is a psychological factor effecting the improvement of motor skills. The present study was aimed to examine the effect of mental imagery and physical exercise on static balance in subjects with Multiple sclerosis (MS). Materials and methods: In this quasi experimental study, all male patients with MS (n = 300) in Ahvaz province (n = 300) were recruited. Kinesthetic and visual imagery questionnaire (KVIQ) was distributed among them to select a suitable sample size. In next step, thirty three individuals with the same imagery ability and expanded disability status scale (EDSS) were chosen and randomly and equally classified in three groups of mental imagery-physical exercise(combined) (n = 11), mental imagery (n = 11), and physical exercise (control) (n = 11). Participants carried out the selected training program three times a week (for 6 weeks). After 2-week, retention test was completed in last training session. The modified Romberg balance test (MRBT) was used to assess static balance in pre-test, post-test, and retention-test. Data, then were analyzed by SPSS, version 16. Results: The results showed that, after 18 sessions, there was a significant difference between post-test (P = 0.01) and retention test (P = 0.001) in different groups; and combined group had a better performance in both stages. Conclusion: According to the results, mental imagery could be used as a practical method for better static balance performance in individuals with multiple sclerosis. Key Words: Mental imagery, Physical exercise, Static balance, Multiple sclerosis